Perspectives on the History of Global Development - Borowy, Iris; Unger, Corinna R.; Ferns, Nicholas; Loveridge, Jack (Yearbook for the History of Global Development, 2022)
What is development, what has it been in the past, and what can historians learn from studying the history of development? How has the field of the history of development evolved over time, and where should it be going in the future?